2006
DOI: 10.1055/s-2006-951748
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Anti-HIV-1 Caged Xanthones from the Resin and Fruits of Garcinia hanburyi

Abstract: Three new caged xanthones, 7-methoxydesoxymorellin (1), 2-isoprenylforbesione (2) and 8,8a-epoxymorellic acid (3), together with nine known caged xanthones were isolated from the EtOAc extracts of resin and fruits of Garcinia hanburyi. The structures were determined by spectroscopic methods. Most of the isolated compounds showed significant cytotoxicities against a panel of mammalian cancer cell lines. Compound 3, together with the known compounds desoxymorellin, morellic acid, gambogic acid, hanburin, forbesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 20 publications
0
81
0
Order By: Relevance
“…A major constituent in gamboge is gambogic acid (11), the chemical structure of which was reported by Ollis et al (1965). Gambogic acid was found not only in the resin but also the whole plant (Lu et al, 1984) and fruits (Reutrakul et al, 2007). More than 40 caged xanthones were discovered from the resin of this plant as shown in Table 1 and Figure 2.…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 82%
See 1 more Smart Citation
“…A major constituent in gamboge is gambogic acid (11), the chemical structure of which was reported by Ollis et al (1965). Gambogic acid was found not only in the resin but also the whole plant (Lu et al, 1984) and fruits (Reutrakul et al, 2007). More than 40 caged xanthones were discovered from the resin of this plant as shown in Table 1 and Figure 2.…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 82%
“…Natural sources of prenylated caged xanthones. Plants Parts Caged xanthones G. morella (Figure 2) seeds desoxymorellin (1), morellin (2), morellinol (6), dihydroisomorellin (22), moreollin (25), isomoreollin (26) (Adawadkar et al, 1976;Bhat et al, 1964;Kartha et al, 1963;Rao, 1937;Subba et al, 1978) resin isomorellin (3), morellic acid (4), isomorellic acid (5) (Karanjgaonkar et al, 1966;) G. hanburyi (Figure 2) resin desoxymorellin (1), isomorellin (3), morellic acid (4), isomorellic acid (5), isomorellinol (7), morellin dimethyl acetal (8), gambogin (9), gambogic aldehyde (10), gambogic acid (11), epigambogic acid (12), isogambogic acid (13) (Asano et al, 1996;Feng et al, 2008;Han et al, 2006aHan et al, , 2006bHan et al, , 2006cLee & Chen, 2006;Lin et al, 1993;Ollis et al, 1965;Reutrakul et al, 2007;Tao et al, 2009;Wang et al, 2008a) fruits desoxymorellin (1), isomorellin (3), morellic acid (4), isomorellinol (7), gambogic acid (11), 8,8a-epoxymorellic acid (21), dihydroisomorellin (22), isomoreollin B (23), moreollic acid (27), hanburinone (33), forbesione (39), 2-isoprenylforbesione (desoxyqaudichaudione A) (40), desoxygambogenin (43) (Reutrakul et al, 2007;Sukpondma et al, 2005a) whole plant gambogic acid (11), neogambogic acid (35) (Lu et al, 1984) G. forbesii (Figure 2) branches forbesione (39) (Leong et al, 1996) G. gaudichaudii (Figure 3) leaves morellic acid (4), forbesione (39), gaudichaudiones A-H (53-60), gaudichaudiones I-J (61-62), gaudichaudiic acids A-E (63-67) (Cao et al, 1998a(Cao et al, , 1998bWu et al, 2000) barks gaudichaudiic acids F-I (68-71), 7-isoprenylmorellic acid (72) (Wu et al, 2001;Xu et al, 2000 Garcinia hanburyi has been reported as a rich source of cytotoxic caged xanthones. Its orange gum-resin from stem bark, gamboge, is used in Thai traditional medicine as a purgative and an anthelm...…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 99%
“…Coumarins are a class of lactones which are found widely in nature and possess antiinflammatory [1,2], antiviral [3], antiHIV [4], antifungal [5] and cytotoxic activities [6,7], which have been reviewed [8]. In the development of newer antimicrobials, coumarins have been identified as target specific plant anti-bacterial agents with growth inhibitory potential particularly against Gram-positive species [9].…”
Section: Introductionmentioning
confidence: 99%
“…1) was extracted from G. hanburyi Hook. f. (family Guttiferae) using bioassay-directed fractionation (10). Forbesione was dissolved in dimethyl sulfoxide (DMSO) to create a stock solution of 1.8 mM that was stored at -20˚C.…”
Section: Methodsmentioning
confidence: 99%
“…f. (family Guttiferae), which have been used in Thai traditional medicine (6,7). Gambogic acid, forbesione, isomorellin and isomorellinol, the caged xanthones isolated from G. hanburyi, are reported to exhibit antitumor activities (8) and cytotoxic effects in several cancer cell lines (8)(9)(10). Gambogic acid is the most intensively studied caged xanthone, and exhibits potent antitumor activity in vitro and in vivo (11)(12)(13) through several mechanisms, including inhibition of topoisomerase II alpha activity (14), downregulation of telomerase (15), induction of cell cycle arrest (16) and induction of apoptosis (17).…”
Section: Introductionmentioning
confidence: 99%